Septiņgadīgu bērnu ar smagiem garīgiem attīstības traucējumiem adaptācija skolā - Kalniņa, Jeļena (Latvijas Universitāte, 2019)
. Diplomdarba tēma ir „Septiņgadīgu bērnu ar smagiem garīgiem attīstības traucējumiem adaptācija skolā.” PĒTĪJUMA MĒRĶIS: izpētīt septiņgadīgu bērnu ar smagiem garīgās attīstības traucējumiem adaptāciju skolā. PĒTĪJUMA OBJEKTS: septiņgadīgo bērnu ar smagiem garīgās attīstības traucējumiem adaptācijas process skolā. PĒTĪJUMA PRIEKŠMETS: septiņgadīgu bērnu ar smagiem garīgās attīstības traucējumiem adaptācijas iespējas.. Darba teorētiskā daļā tiek pētīta un analizēta literatūra par bērniem ar smagiem garīgas attīstības traucējumiem, saskarsmes prasmju un attīstības īpatnības, ievērojot septiņgadīgu bērnu veselības stāvokli un attīstības līmeni. Praktiskā daļā tiek pētīti bērni ar smagiem garīgās attīstības traucējumiem, sākot no dzimšanas līdz septiņiem gadiem. Diplomdarba autore iepazinās ar medicīniskām kartēm, runāja ar bērnu vecākiem un pati pētīja bērnus sākot no 01.09. 2017.gada, veicot vērojumus bērna attīstībā, uztverē, domāšanā, komunikācijā ar pārējo sabiedrību. Diplomdarba autore balstās arī uz savu darba pieredzi internātpamatskolā bērniem ar smagiem garīgās attīstības traucējumiem. DARBA AUTORE: Jeļena Kalniņa un darba vadītāja doc. Dr. paed. Rasma Vīgante. DARBA STRUKTŪRA: ievads, trīs nodaļas ar apakšnodaļām, nobeigums, izmantotā literatūra un avoti( 51 vienības), trīs pielikumi. ATSLĒGAS VĀRDI: septiņgadīgie bērni, adaptācija skolai, smagi garīgās attīstības traucējumi.

ANOTATION. The theme of the diploma paper is "Adaptation of seven-year-old children with severe mental disorders in school" PURPOSE OF THE RESEARCH:Study the adaptation of a seven-year-old child with severe mental development problems at school. RESEARCH OBJECT: Adaptation process for seven-year-old children with severe mental disorders in primary school. SUBJECT OF THE RESEARCH: seven-year-old children with severe mental disorders beginning of the school attendance. The final assignment’s theoretical part includes studying and analyzing literature about children with severe mental disorders, their skills of communication and development peculiarities observing the health status and level of development. In the practical part, children with severe mental disorders from birth to seven years are studied.The author of the final assignment got acquainted with medical cards, spoke with parents of children and studied children themself from September 1st, 2017, observing the child's development, perception, thinking, and communication with the rest of society.The author also based her arguments on her working experience at a boarding school with serious mental disorders for children. AUTHOR: Jeļena Kalniņa. Supervisor Dr. paed. Rasma Vīgante. STRUCTURE OF THE WORK: introduction, three chapters with subdivisions, final, used literature and sources 51 units, 3 appendices: KEY WORDS: seven-year-olds, adaptation to school, severe mental disorders. ANOTATION. The theme of the diploma paper is "Adaptation of seven-year-old children with severe mental disorders in school" PURPOSE OF THE RESEARCH:Study the adaptation of a seven-year-old child with severe mental development problems at school. RESEARCH OBJECT: Adaptation process for seven-year-old children with severe mental disorders in primary school. SUBJECT OF THE RESEARCH: seven-year-old children with severe mental disorders beginning of the school attendance. The final assignment’s theoretical part includes studying and analyzing literature about children with severe mental disorders, their skills of communication and development peculiarities observing the health status and level of development. In the practical part, children with severe mental disorders from birth to seven years are studied.The author of the final assignment got acquainted with medical cards, spoke with parents of children and studied children themself from September 1st, 2017, observing the child's development, perception, thinking, and communication with the rest of society.The author also based her arguments on her working experience at a boarding school with serious mental disorders for children. AUTHOR: Jeļena Kalniņa. Supervisor Dr. paed. Rasma Vīgante. STRUCTURE OF THE WORK: introduction, three chapters with subdivisions, final, used literature and sources 51 units, 3 appendices: KEY WORDS: seven-year-olds, adaptation to school, severe mental disorders. ANOTATION. The theme of the diploma paper is "Adaptation o
Adaptation of seven-year-old with severe mental disorders in school
Keywords: Pedagoģija; septiņgadīgie bērni; adaptācija skolai; smagi garīgās attīstības traucējumi.; bērni